2020
DOI: 10.1016/j.thromres.2020.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 associated autoimmune thrombotic thrombocytopenic purpura: Report of a case

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 10 publications
0
60
0
4
Order By: Relevance
“…ADAMTS13 antigen activity level and antibody confirmed the diagnosis of TTP. She received daily plasma exchange and methylprednisolone [40] . Capecchi et al reported a 55-year-old woman with a previous TTP history associated with bacterial pneumonia, thirty years ago.…”
Section: Discussionmentioning
confidence: 99%
“…ADAMTS13 antigen activity level and antibody confirmed the diagnosis of TTP. She received daily plasma exchange and methylprednisolone [40] . Capecchi et al reported a 55-year-old woman with a previous TTP history associated with bacterial pneumonia, thirty years ago.…”
Section: Discussionmentioning
confidence: 99%
“…vWF is released from both endothelial cells and platelet storage granules and mediates platelet adhesion to the endothelium. Evaluation of circulating vWF multimers in patients with COVID-19 might be informative because COVID-19 pathology has signatures of thrombotic thrombocytopenia purpura, which is characterized by thrombocytopenia, microthrombi, endothelial cell dysregulation and increased circulating levels of vWF multimers 224,225 . Elevated circulating levels of vWF seem to have prognostic relevance in COVID-19, being associated with severe disease 69 .…”
Section: Cardiovascular Risk Factors and Covid-19mentioning
confidence: 99%
“…However, viral infections are well described triggers of TTP cases [ 2 ], and SARS-CoV2 have been described in correlation with different autoimmune and inflammatory diseases in both children and adults [ 3 ]. Finally, two cases of TTP were recently reported in patients diagnosed with COVID-19 [ 4 , 5 ]. In both cases, thrombotic microangiopathy presented six days after initial symptoms of viral infection and COVID pneumonia was mild.…”
mentioning
confidence: 99%